Who is at a Higher Risk? A brief review of Recent Evidence on comorbidities in children infected with COVID-19. - Qamar, Mohammad Aadil; Sajid, Mir Ibrahim; Dhillon, Rubaid Azhar; Irfan, Omar; Abaidullah, Sajid (Journal of Ayub Medical College Abbottabad, 2021)
Background: COVID-19 has affected both adults and children with variable presentations and disease severity. Children can present with mild symptoms of fever, cough and shortness of breath, and rapidly progress to severe pneumonia, requiring mechanical ventilation. This population includes children who are younger than one year and older adolescents who have an underlying comorbidity-specifically immunosuppression or prior cardio-respiratory infections. In this review, we discuss the determinants of severe disease among the paediatric patients- primarily asthma, immune-status, obesity and multisystem inflammatory syndrome in children (MIS-C). Asthma and underlying lung pathologies can be a strong predictor (~20% prevalence) for development of severe COVID-19 infection, irrespective of age. However, as compared to asthma, a higher mortality rate was reported in immune-compromised patients. With a weakened immune system, immunosuppressed individuals were 1.55 times and immunocompromised patients 3.29 times more vulnerable to developing severer COVID-19 disease. Similarly, evidence suggests that a BMI of greater than 35 kg/m2 renders individuals more susceptible to developing COVID-19-related complications. This observation is based on the negative impacts obesity has on pulmonary functions and in downplaying the immune system. Furthermore, a possible association of COVID-19 and MIS-C has been reported by multiple studies across the globe but it needs further studies to strengthen its stance due to the scarcity of data when compared with the other determinants discussed in this article. Authors recommend researchers directing attention on synthesizing the evolving evidence to fill the knowledge void in the paediatric population, which will better enable paediatricians to make informed decisions. Keywords: COVID-19; children; asthma; immunosuppression; obesity; comorbidities